Unraveling the immunological landscape in acute pancreatitis progression to sepsis: insights from a Mendelian randomization study on immune cell traits - Liu, Wenbin; Wang, Xiaofeng; Zhao, Shanzhi; Yang, Song; Zheng, Xiangtao; Gong, Fangchen; Pei, Lei; Xu, Dan; Li, Ranran; Yang, Zhitao; Mao, Enqiang; Chen, Erzhen; et al. (Frontiers in Immunology, 2024)
Background Acute pancreatitis (AP) is a severe digestive system disorder with a significant risk of progressing to sepsis, a major cause of mortality. Unraveling the immunological pathways in AP is essential for developing effective treatments, particularly understanding the role of specific immune cell traits in this progression. Methods Employing a bidirectional two-sample Mendelian Randomization (MR) approach, this study first examined the causal relationship between AP and 731 immune cell traits to identify those significantly associated with AP. Subsequently, we explored the causal associations between 731 immune cell traits and sepsis. The analysis utilized extensive genome-wide association studies (GWAS) summary datasets, with a focus on identifying common immune cell traits with statistically significant causal associations between AP and sepsis. Results Our investigation identified 44 immune cell traits unidirectionally associated with AP and 36 traits unidirectionally associated with sepsis. Among these, CD127 on CD28+ CD45RA- CD8+ T cells emerged as a common mediator, accounting for 5.296% of the increased risk of sepsis in AP patients. This finding highlights the significant role of specific memory CD8+ T cells in the pathophysiology of AP and its progression to sepsis. Conclusion This study elucidates the critical role of specific immune cell traits, particularly CD127hi memory CD8+ T cells, in the progression of AP to sepsis. Our findings provide a foundation for future research into targeted immune-modulatory therapies, potentially improving patient outcomes in AP-related sepsis and offering new insights into the complex immunological dynamics of this condition.